Pemanfaatan Ekstrak Bekatul Beras Merah Sebagai Sumber Prebiotik Dalam Pembuatan Yoghurt Dengan Variasi Lama Fermentasi - Rofiah, Nur Fatakhu; , Dr. Nanik Suhartatik, S.TP., M.P (2015)
Red rice bran has great benefits to health that have a high content of Vitamin B15 or pangamic acid highest compared with other crops. Yogurt is a dairy products are processed through fermentation and has a sour taste specific. The purpose of this study was to determine the protein content and the amount of red rice bran yogurt bacteria from red rice bran levels and variations fermentation. This study uses two treatment that red rice bran extract 10 g / 100 cc (N1), 20 g / 100 cc (N2), 30 g / 100 cc (N3) with fermentation time 4 hours (K1), 6 hours (K2) , 8 hours (K3). The result showed that the highest protein content is in treatment N3K1 (red rice bran extract concentration of 30 g / 100 cc with fermentation time 4 hours), ie with an average of 5.88 g. For the lowest protein content is in treatment N1K2 (red rice bran extract concentration of 10 g / 100 cc with fermentation time 6 hours) is the average of 3.865 g. For most number of bacteria in the treatment N1K2 (red rice bran extract concentration of 10 g / 100 cc with fermentation time 6 hours) is the number more than 109, and the least in the treatment N2K1 (red rice bran extract concentration of 20 g / 100 cc with fermentation time 4 hours), namely the number of 1.42 × 10.